Out-of-school science activities - Retrospect and prospect in the Caribbean - King, Winston K. (Commission for Biological Education, International Union of Biological Sciences, 1984)
This paper formulates 11 aims of out-of-school science in the Caribbean, discusses their implications for finance, examinations, curriculum development, and teacher training, and describes some out-of-school science activities in the Caribbean. These are classified as: activities emphasizing applied sciences; science teachers' associations, science projects, and exhibitions; clubs and societies; and regional associations
Keywords: Scientific activities